What are linguistic representations?. (18th April 2022) - Adger, David
Abstract : Linguistic representations are taken by some to be representations of something, specifically of standard linguistic entities (SLEs), such as phonemes, clauses, noun phrases, and so forth. This perspective takes them to be intentional. Rey further argues that the SLEs themselves are inexistent. Here I argue that linguistic representations are simply structures, abstractions of brain states, and hence not intentional, and show how they nevertheless connect to the systems that use them.